Dynamics of Strengthening Character Education for Students at SMA Negeri 1 Aikmel East Lombok - Badarudin Badarudin; Ahmad Tohri; Mashun Mashun; Husnul Hairi (Universitas Hamzanwadi, 2025)
This study aims to analyze how the planning, implementation, and evaluation process on strengthening the character education of students at SMAN 1 Aikmel, East Lombok. This research uses a qualitative approach, with a descriptive qualitative type. The research site was at SMAN 1 Aikmel, East Lombok, with the subject of the research being the principal and the research informants being the student affairs and teachers. While the data collection technique uses observation, interview and documentation techniques, the data validation technique is carried out by triangulation, namely the triangulation technique of data sources and methods, then the data analysis technique is carried out in several stages, namely data collection, data reduction, data display and conclusions drawing or verifying. The results of this study obtained an overview that: first, planning has been carried out as best as possible starting from the program planning meeting of goal formulation, strategy preparation, policy determination, procedure mapping, and program improvement involving all components of the school, deputy principal for curriculum, student affairs, infrastructure, public relations, treasurer, educators and education staff and school committees.; Second, the implementation of strengthening the character of students runs well through organizing activities and actions focusing on the character values of students; Third, the evaluation of the process of strengthening students' character education through activities to supervise the implementation of activities, reflect, analyze and follow up.